2019
DOI: 10.1021/acsomega.9b02236
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Curcumin Improve Intestinal Mucosal Integrity and Decrease m6A RNA Methylation in the Intestine of Weaning Piglets

Abstract: N6-Methyladenosine (m6A) is the most prevalent modification on eukaryotic messenger RNA (mRNA). Resveratrol and curcumin, which can exert many health-protective effects, may have a relationship with m6A RNA methylation. We hypothesized that the combination of resveratrol and curcumin could affect growth performance, intestinal mucosal integrity, m6A RNA methylation, and gene expression in weaning piglets. One hundred and eighty piglets weaned at 28 ± 2 days were fed a control diet or supplementary diets (300 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…In addition, mice in the RES group exhibited a significant reduction of METTL3 protein expression and a prominent increase of FTO protein expression. Consistent with our previous study, resveratrol was able to reduce the abundance of m 6 A modification in piglets [47]. Therefore, these data suggest that the protective function of resveratrol against AFB 1 -induced liver damage is related to the reduction of m 6 A modification.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, mice in the RES group exhibited a significant reduction of METTL3 protein expression and a prominent increase of FTO protein expression. Consistent with our previous study, resveratrol was able to reduce the abundance of m 6 A modification in piglets [47]. Therefore, these data suggest that the protective function of resveratrol against AFB 1 -induced liver damage is related to the reduction of m 6 A modification.…”
Section: Discussionsupporting
confidence: 92%
“…Between 21 and 28 days of age, they were fed a basal diet supplemented with: 300 mg/kg of resveratrol (W-RSV), 300 mg/kg of pterostilbene (W-PT), or no supplementation (W-CON). The dosages of resveratrol and pterostilbene added to the diet of weaned piglets were selected based on an independent pre-study, as well as the results reported by our colleagues and other groups [29,30]. A greater degree of feed efficiency was observed for weaned piglets between the ages of 21 and 42 days when pterostilbene was provided at 250 or 500 mg/kg of diet (unpublished).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…A greater degree of feed efficiency was observed for weaned piglets between the ages of 21 and 42 days when pterostilbene was provided at 250 or 500 mg/kg of diet (unpublished). Resveratrol has been proven to improve the jejunal antioxidant ability of weaned piglets at 42 days of age and prevent the muscular lipid peroxidation of finishing pigs at slaughter [29,30]. Therefore, the same dose, 300 mg/kg, was selected for both resveratrol and pterostilbene in this study.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Another possibility currently explored in our laboratory is that I 2 as an oxidized agent can exert epigenetic modifications associated with the activation of important demethylase enzymes like DMT3 [ 101 ], unpublished results). In fact, other natural antioxidants, such as resveratrol or curcumin, exert part of their effects by modifying the methylation/demethylation equilibrium genes for the differentiation of Th1 (T-bet and STAT4) or Th2 (GATA3) [ 102 ].…”
Section: Introductionmentioning
confidence: 99%